2021
DOI: 10.5312/wjo.v12.i10.781
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effectiveness of high- and low-intensity percutaneous electrolysis in patients with patellofemoral pain syndrome: A pilot study

Abstract: BACKGROUND Unilateral patellofemoral pain syndrome (PFPS) is the most frequently diagnosed knee condition in populations aged < 50 years old. Although the treatment of myofascial trigger points (MTrPs) is a common and effective tool for reducing pain, previous studies showed no additional benefits compared with placebo in populations with PFPS. Percutaneous electrolysis is a minimally invasive approach frequently used in musculotendinous pathologies which consists of the application of a galvanic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…In fact, no significant differences were found between low- and high-intensity groups. Those results are coherent with the pilot study conducted by Valera-Calero et al [ 45 ], which is the only one to date (to the best of our knowledge) comparing two PE protocols in humans. They found no differences between protocols in sensitivity and pain in patients with patellofemoral pain syndrome.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, no significant differences were found between low- and high-intensity groups. Those results are coherent with the pilot study conducted by Valera-Calero et al [ 45 ], which is the only one to date (to the best of our knowledge) comparing two PE protocols in humans. They found no differences between protocols in sensitivity and pain in patients with patellofemoral pain syndrome.…”
Section: Discussionsupporting
confidence: 92%
“…The full article was then accessed and three articles were removed as two of them had no final results [24,38] and one [39] used pulsed current. Finally, a total of six articles were included in the qualitative and quantitative analysis of our review [22,23,25,[40][41][42]. The study selection flow diagram is shown in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
“…The included studies were highly heterogeneous as they studied different musculoskeletal conditions. These were tendinopathy of the supraspinatus [43], lateral epicondylalgia [41] temporomandibular pain [40], plantar pain [23], patellar tendinopathy [25], and patellar pain syndrome [42].…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, the choice of the dosage of administration of PE therapy is poorly supported by scientific evidence. To the best of our knowledge, only a pilot study has compared two PE protocols in patients, finding no differences between them in sensitivity and pain associated with patellofemoral pain syndrome ( 42 ). In this case, the two protocols presented little variation in the intensity parameter (0.220 mA for 30 s and 0.660 mA for 10 s) and both would belong to the low-intensity modality.…”
Section: Discussionmentioning
confidence: 99%